Nonlinear TE Electromagnetic Surface Waves in a Ferrite Layered Structure - Khetam El-Wasife; Mohammad Shabat; Sameer Yassin (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Characteristics of TE electromagnetic surface waves propagating in a nonlinear dielectric film bounded by a ferrite cover are examined theoretically. A dispersion relation based on Jacobian Elliptic Functions is derived, which describes the behaviour of the nonreciprocal nonlinear waves.